Histological and Histochemical Analysis of Austrocedrus chilensis Trees Healthy and Infected with Phytophthora austrocedri - Troncoso, Oscar Alberto (2025)
The endemic Patagonian conifer, Austrocedrus chilensis, is threatened by the pathogenPhytophthora austrocedri. This study presents the first histological and histochemical analysisof A. chilensis affected by this pathogen. We examined the stem tissues of naturally infectedadult trees (over 30 years old) and artificially inoculated saplings (8–12 years old) to identifythe pathogen’s colonization strategies and the tree’s histological responses. Using lightand scanning electronic microscopy along with several histochemical techniques (Lugol,toluidine blue, vanillin-HCl, Phloroglucinol, Calcofluor white, and aniline blue), we foundthat P. austrocedri can grow in all active tissues, leading to cambium and parenchymanecrosis. The pathogen spreads through sieve cells and tracheids, moving to the adjacentcells via sieve plates and bordered pits and colonizing nearby parenchyma cells. Weobserved loss of starch in necrotic tissues. In contrast, starch accumulation and an increasein the number of polyphenolic cells occur in the healthy areas adjacent to the margins ofthe lesion, indicating a tree’s induced defense mechanisms. The tree’s responses includecambium reprogramming, which leads to the formation of traumatic resin ducts, alterationsin cell shape and size, and the deposition of phenolic compounds. We analyze the treeresponses and discuss their potential relationship with a methyl jasmonate-induced defenseand a hypersensitive-like response.